Avaliação da pesquisa de anticorpos antifosfolipídios para o diagnóstico da síndrome antifosfolípide - Perches, Paula Gonçalves (2009)
OBJECTIVE: To evaluate the prevalence of lupus anticoagulant (LAC) and isotypes of anticardiolipin (ACL) antibodies and its possible clinical associations. PATIENTS AND METHODS: A retrospective study analyzed clinical and laboratorial manifestations in individuals who showed positive antiphospholipid antibodies followed-up at Hospital Edmundo Vasconcelos from March 2005 to June 2006. RESULTS: 106 participants (mean age of 42.2 ± 14.1 years at inclusion and female gender in 84% of patients) were included in the study. The prevalence of thrombosis was 17.9% (19/106 patients) and pregnancy morbidity was 12.3% (13/106 patients). The antiphospholipid syndrome (APS) was confirmed in 23.6% (25/106 patients), and it was primary in 68% (17/25 patients) and secondary in 32% (8/25 patients). The ACL antibodies were found in 97.1% (103/106) and LAC in 11.4% (5/44 of the serum samples tested). IgM, IgG and IgA ACL isotypes were respectively found in 100%, 23.3% and in 4.9% of these ACL positive sera. For APS diagnosis the sensitivity of IgM ACL was 92% and its specificity was 1.2%, while IgG ACL had a sensitivity of 40% and specificity of 82.5%. The absence of IgG ACL had a high negative predictive value for APS diagnosis (81.4%).The analysis of the Receiver Operating Characteristic (ROC) curve showed larger area under the curve for ACL IgG and LAC. CONCLUSION: In a random sample of individuals with positive antiphospholipid antibodies, IgG ACL and LAC showed a larger specificity for APS diagnosis which had been characterized by a higher prevalence of thrombosis.